DIGITAL READINESS INFLUENCE ON MOBILE ADVERTISING ACCEPTANCE AMONG MILLENIALS - Azzahra, Dwine Fatimah; Nasution, Reza Ashari (Journal of Business and Management, 2017)
Abstract.Background: This research explores influences of digital readiness on acceptance of mobile advertising. Millennial generation is used as object for this research considering their closeness to digital technology. Digital readiness is tested if it can become the antecedent of TAM. Since the context used is mobile advertising, adoption of technology is changed to acceptance because people are more likely accepting mobile advertising rather than adopting. This research constructs new model based on readiness theory and Technology Acceptance Model (TAM) using survey that personally distributed to young Millennials who covers several regions in Java. Methods: Structural Equation Modelling (SEM),Results: Digital readiness has strong influence towards mobile advertising acceptance among Millennials. This research also compares results based on the age group of Millennials and generates different results on correlations between variables.Conclusion: Millennials in Java have readiness in terms of beliefs and abilities on accepting mobile advertising among them. Nevertheless, their behaviors on accepting mobile advertising are different between age groups. Marketers can use the results as their consideration to set the strategy for different segment of Millennials. Keywords:  Digital Readiness, Millennials Generation, Mobile Advertising, Structural Equation Model (SEM), Technology Acceptance Model.